MEMORI TRAUMA DALAM FILM G30S/PKI: SEBUAH INTERPRETASI TEOLOGIS - John C. Simon (Prodi Studi Agama-Agama, 2021)
This article is motivated by the polemic surrounding watching the G30S/PKI film. The purpose of writing is to find new insights from film as one of the artifacts of popular culture: where film is a mirror of oneself, even a mirror of a nation. Through an effort to analyze the film Peng betrayan G30S/PKI, we capture a moral message about the gripping culture of a society that has suffered from chronic and traumatic historical wounds for so long. Through this film, we find a picture of power that appears as an “interpretation regime”, which monopolizes and controls the interpretation of the world of signs and symbols, namely the G30S/PKI film, so that the truth is bent for the sake of political propaganda. With a qualitative method, this paper intends to construct emancipatory meanings through reading films that speak of small narratives that function as trauma healers, and whose presence becomes an opponent for the domination of the big narratives of a nation's history. The results of this study confirm that the trauma passed down from generation to generation is faced not by running from it, but rather by facing it, re-watching it, making it a mirror of our own modesty in the past. It can be concluded that the narrative of a film is a means to restore spiritual shame, so that we can appreciate the shame of failing before God, to be restored and empowered again as a new human being.